Fostering Literacy Development through the Use of Big Books in a Group of First Graders at a Public Institution (2022)
ABSTRACT: This action research project was developed to explain in what ways the use of big books can promote literacy development in a group of first-graders at a public institution in Medellín. This project was carried out in a group of 41 students between boys and girls. In the action plan, a big book reading aloud strategy was implemented during the first semester of the academic year. Data were collected through an interview, student's artifacts, and a journal. Findings showed thatthe young students of this group responded in a very positive way to reading aloud and that the use of big books boosted their literacy process in combination with hands-on activities. Data also displayed environmental factors of the institution that significantly affected their levels of attention and their learning proces.